A history of Russia, Central Asia and Mongolia. Volume II, Inner Eurasia from the Mongol Empire to today, 1260-2000 - Christian, David, 1946- 4 0 16; 5 (Hoboken, NJ : Wiley Blackwell, 2018)
Beginning with the breakup of the Mongol Empire in the mid-thirteenth century, Volume II of this comprehensive work covers the remarkable history of Inner Eurasia, from 1260 up to modern times, completing the story begun in Volume I. Volume II describes how agriculture spread through Inner Eurasia, providing the foundations for new agricultural states, including the Russian Empire. It focuses on the idea of mobilization--The distinctive ways in which elite groups mobilized resources from their populations, and how those methods were shaped by the region's distinctive ecology, which differed greatly from that of Outer Eurasia, the southern half of Eurasia and the part of Eurasia most studied by historians. This work also examines how fossil fuels created a bonanza of energy that helped shape the history of the Communist world during much of the twentieth century. Filled with figures, maps, and tables to help give readers a fuller understanding of what has transpired over 750 years in this distinctive world region, A History of Russia, Central Asia and Mongolia: Volume II: Inner Eurasia from the Mongol Empire to Today, 1260-2000 is a magisterial but accessible account of this area's past, that will offer readers new insights into the history of an often misunderstood part of the world. --
Inner Eurasia in the Agrarian Era: 1260-1850. Inner Eurasia in the Late Thirteenth Century: The Mongol Empire at its Height -- 1260-1350: Unraveling and the Building of New Polities -- 1350-1500: Central and Eastern Inner Eurasia -- 1350-1500: Western Inner Eurasia -- 1500-1600: Pastoralist and Oasis Societies of Inner Eurasia -- 1500-1600: Agrarian Societies West of the Volga -- 1600-1750: A Tipping Point: Building a Russian Empire -- 1600-1750: A Tipping Point: Central and Eastern Inner Eurasia between Russia and China -- 1750-1850: Evolution and Expansion of the Russian Empire -- Inner Eurasia in the Era of Fossil Fuels: 1850-2000. 1850-1914: The Heartland: Continued Expansion and the Shock of Industrialization -- 1750-1900: Beyond the Heartlands: Inner Eurasian Empires, Russian and Chinese -- 1914-1921: Unraveling and Rebuilding -- 1921-1930: New Paths to Modernity -- 1930-1950: The Stalinist Industrialization Drive and the Test of War -- 1900-1950: Central and Eastern Inner Eurasia -- 1950-1991: The Heartland: A Plateau, Decline, and Collapse -- 1950-1991: Beyond the Heartlands: Central and Eastern Inner Eurasia in the Second Half of the Twentieth Century -- 1991-2000: Building New States: General Trends and the Russian Federation -- 1991-2000: Building New States: Beyond the Heartlands -- Epilogue: After 2000: The End of Inner Eurasia? -- Chronology.
Includes index.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed January 10, 2018).
Keywords: 2 -- 0; 6; 20; History.;History.;History. -- Former Soviet republics;Mongolia;Xinjiang Uygur Zizhiqu (China) -- 20; Electronic books.;History.